PENGARUH PEMBERIAN INSENTIF DAN MOTIVASI KERJA TERHADAP SEMANGAT KERJA KARYAWAN (SURVEY PADA KOPTI KABUPATEN KUNINGAN) - Arraniri, Iqbal; Izatunnisa, Riza (Universitas Kuningan, 2018)
The purposes of this research are: (1) description of giving incentives and work motivation and morale at KOPTI Kuningan Regency (2) Influence of giving incentive to morale at KOPTI employees of Kuningan Regency (3) Influence of work motivation to morale at KOPTI employees of Kuningan Regency (4) Effect of incentive and work motivation on employee morale at KOPTI Kuningan Regency. This research uses descriptive method. The population in this research is all employees of KOPTI Kuningan District as many as 30 people, with sampling technique using saturated sampling technique. Data were collected with questionnaires that have been tested for validity and reliability. Data analysis technique used is multiple linear regression. The results of this study show that: (1) Description of incentives and motivation of work and morale included in being and high category. (2) Incentive has a positive effect on employee morale (3) Work Motivation has a positive effect on employee morale (4) provision of incentives and work motivation have a positive effect on morale and can be written with regression equation = 24,861 + 0,216X1 + 0,598X2 with magnitude effect of 77.0% and the remaining 23.0% influenced by other factors outside the research model. Keywords: Incentives, Work Motivation, Employee Morale